2015
DOI: 10.1177/239700221502900204
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Management in Professional Services Firms: Too Good to Be True? Transcending Conflicting Institutional Logics

Abstract: Why is it that HR specialists appear to have difficulty applying their knowledge, systems and techniques in a systematic way when it comes to professional services firms (PSFs)-particularly when the drivers for developing powerful HRM practices within such businesses seem more pressing than ever? This paper analyzes the ways HR specialists and PSF managers/partners differ in their understanding of organizations and their management. The analysis supports the argument that, while HR specialists and the discipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 40 publications
(50 reference statements)
1
24
0
Order By: Relevance
“…We thus need to reconsider the notion of context, and to extend it beyond how it has been used in the contemporary HRM literature, especially the transfer literature regarding MNCs (e.g. Ahlvik & Bj€ orkman, 2015;Ahlvik, Smale, & Sumelius, 2016), which has focused on comparing institutional arrangements between countries and has thus considered cross-national variations to be the main contextual factor (see Almond, 2011;B evort & Poulfelt, 2015). Thus, critical HRM is helpful in redirecting the focus towards everyday practice (Watson, 2004) and the local organizational context in which the negotiated nature of HR practices unfolds (Delbridge et al, 2011;Jenkins & Delbridge, 2013;Thompson, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus need to reconsider the notion of context, and to extend it beyond how it has been used in the contemporary HRM literature, especially the transfer literature regarding MNCs (e.g. Ahlvik & Bj€ orkman, 2015;Ahlvik, Smale, & Sumelius, 2016), which has focused on comparing institutional arrangements between countries and has thus considered cross-national variations to be the main contextual factor (see Almond, 2011;B evort & Poulfelt, 2015). Thus, critical HRM is helpful in redirecting the focus towards everyday practice (Watson, 2004) and the local organizational context in which the negotiated nature of HR practices unfolds (Delbridge et al, 2011;Jenkins & Delbridge, 2013;Thompson, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Delbridge & Keenoy, 2010;Delbridge et al, 2011;Keegan & Boselie, 2006), and its call for more contextualized and non-managerialist research that gives voice to multiple organizational actors. While much of the contemporary HRM literature has focused on cross-national variations as its main contextual factor (see Almond, 2011;B evort & Poulfelt, 2015), we highlight the importance of local organizational contexts in our aim of understanding the contextual embeddedness of HR practices. We also emphasize social relationships, with cultural values as root causes of how and why actors engage with HR practices as they do, in contrast to the rational explanation, as adopted in much of mainstream HRM (Delbridge et al, 2011;Evans & Tourish, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has identified a need for understanding how HRM works in different contexts (Hauff, Alewell, & Hansen, ; Jackson, Schuler, & Jiang, ). The PSF context presents a challenge because its underlying logic is “fundamentally different” and in conflict with HRM's bureaucratic logic (Bévort & Poulfelt, , p. 125; Kaiser, Kozica, Swart, & Werr, ). PSFs emphasise informal control systems, professional meritocracy, and individual discretion (Adler et al, ; von Nordenflycht, Malhotra, & Morris, ; Wallace, ).…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between professionalism and bureaucracy have been described as involving inherently conflicting or contradictory institutional logics (Pache & Santos, ; Wallace, ). Increasingly, however, PSFs combine several conflicting logics simultaneously (Kirkpatrick & Noordegraaf, )—by introducing elaborate HRM systems (Bévort & Poulfelt, ), for example. Such hybrid arrangements have only recently been discussed, and whereas there is much theorising on conflicts between logics, we know “little about how they coexist, and virtually nothing about how they can positively feed off each other” (Smets, Jarzabkowski, Burke, & Spee, , p. 933).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation